Organization of controlling innovations in an industrial enterprise management - A. R. Khachemizov (Новые технологии)
The purpose of the research is to determine methodological and functional basis of the process of controlling innovations in enterprise management. The article deals with the problem of supporting the process of innovative projects management in the context of analyzing their effectiveness and making strategic decisions in the field of innovative development of an enterprise in the structural and functional environment of the controlling system. The works of scientists in the field of the development of approaches to the organization of controlling served as the methodological basis of the research. The article uses a systematic approach to the consideration of controlling in the enterprise system using the methodological basis of project management. As a result of the research, a scheme has been created representing the role of controlling as an element of feedback in an enterprise system, a description of the main controlling functions as an industrial enterprise management subsystem has been presented, and the role of controlling in the implementation of innovative project management processes has been clarified. It has been established that the formation of the innovation controlling system predicts the construction of an integrated communication structure ensuring collection, processing and provision of objective and reliable information for decision-making, as well as operational communicative interaction between heads of structural divisions and top management in the development and implementation of innovations.